2020
DOI: 10.1007/s00595-020-01963-2
|View full text |Cite
|
Sign up to set email alerts
|

The past, present, and future status of multimodality treatment for resectable/borderline resectable pancreatic ductal adenocarcinoma

Abstract: A multimodal approach to treating pancreatic ductal adenocarcinoma (PDAC) is now widely accepted. Improvements in radiological assessment have enabled us to define resectability in detail. Multimodality treatment is essential for patients, especially for those with PDAC in the borderline resectable (BR) stage. Even for disease in a resectable (R) stage, adjuvant and neoadjuvant therapies have demonstrated beneficial outcomes in several trials and analyses. Thus, there is growing interest in optimization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…21 There have also been improvements in multimodality therapy for pancreatic adenocarcinoma, which have shown a small survival benefit. 22 Emerging data about the efficacy of neoadjuvant chemoradiotherapy followed by surgery and chemotherapy have shown improved 5-year overall survival compared with surgery followed by chemotherapy. 23 Nonetheless, progress in treating pancreatic adenocarcinoma has been incremental at best, as demonstrated by the modest gains in survival over time.…”
Section: Discussionmentioning
confidence: 99%
“…21 There have also been improvements in multimodality therapy for pancreatic adenocarcinoma, which have shown a small survival benefit. 22 Emerging data about the efficacy of neoadjuvant chemoradiotherapy followed by surgery and chemotherapy have shown improved 5-year overall survival compared with surgery followed by chemotherapy. 23 Nonetheless, progress in treating pancreatic adenocarcinoma has been incremental at best, as demonstrated by the modest gains in survival over time.…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary therapy for patients with PDAC is currently being developed 34 . Clinical trials have shown that adjuvant chemotherapy prolongs survival after operation for PDAC 11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…33 Multidisciplinary therapy for patients with PDAC is currently being developed. 34 Clinical trials have shown that adjuvant chemotherapy prolongs survival after operation for PDAC. 11,12 We also demonstrated that the completion of adjuvant chemotherapy was identified as an independent prognostic factor in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the survival of the patients has increased in the last years, PDAC is characterized by comparable incidence and mortality rates, with a 5-year survival after diagnosis around 9% (3). The low survival rate is due to the difficult diagnosis at early stages, resulting in only one fifth of the patients amenable to surgical treatment (4,5). To date, a handful of high penetrance mutations have been associated with increased PDAC risk through family-based studies (3,6).…”
Section: Introductionmentioning
confidence: 99%